Determination of Total Flavonoid Content of Saputangan Leaves (Maniltoa grandiflora (A. Gray) Scheff) and Its Ability as Antioxidant - Jhon Patar Sinurat; Reh Malem Br Karo; Rinaldo Berutu (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Determination of phenolic content using uv-visible and measured IC50 as antioxidant of saputangan leaves. Methods: Screening was used FeCl3, NH3, Alkali and Pb(CH3COO)2. The maceration process was carried out using ethanol as a solvent and soaked for more than 24 hours. The measurement of total flavonoid levels began with determining the maximum wavelength of quercetin, which was 442 nm. The linear regression equation for the resulting quercetin calibration curve was the equation y = 0.0155x + 0.0387 with a correlation value (R2) of 0.9943. The linear regression of antioxidant of saputangan leaves on percentage of inhibition is y = 0.6899x + 1.5616 with a correlation (R2) of 0.9895. The Maniltoa grandiflora (A. Gray) Scheff leaves contained flavonoid compounds which are proven based on the results of screening. Meanwhile, the weight of the extract after partitioning using ethyl acetate and n-hexane was 50 gr. Total flavonoid levels in Maniltoa grandiflora (A. Gray) Scheff leaves were 33.87 mg QE/g extract or 33.87%. IC50 value of 70.2108 ppm which was categorized as an antioxidant at the medium (medium) level. Conclusions: Total flavonoid content was 3.87 mg QE/g extract or 33.87% and categorized as antioxidant on medium level.